The Role of Infrastructure Investment in Driving Regional Economic Growth: A Panel Data Analysis of Emerging Economies - Zulaili, Zulaili; Rahimah, Evida; Putri, Ilfi Rahmi; Suriana, Suriana; Radiah, Radiah (International Journal of Economics (IJEC), 2025)
This study examines the relationship between infrastructure investment and regional economic growth in emerging economies using panel data analysis from 2000-2020. Objectives: To empirically analyze the direct and indirect effects of infrastructure capital stock on economic growth performance across emerging market economies. Methods: We employ a quantitative methodology utilizing panel data econometrics with fixed effects, random effects, and dynamic GMM estimators based on an extended Cobb-Douglas production function framework incorporating infrastructure capital as a third input factor. The sample comprises 45 emerging economies with comprehensive data on GDP per capita, physical capital, human capital, and infrastructure investment indicators. Results: Our findings demonstrate a statistically significant positive relationship between infrastructure investment and economic growth, with an estimated elasticity of 0.24-0.31. The analysis reveals substantial heterogeneity across regions and infrastructure types, with transport and telecommunications infrastructure exhibiting stronger growth effects than water and energy infrastructure. Dynamic models confirm both short-term and long-term positive effects, with infrastructure investment contributing 1.2-1.8 percentage points to annual GDP growth. Conclusions: Infrastructure investment serves as a critical driver of regional economic growth in emerging economies, supporting endogenous growth theory predictions. The results suggest that strategic infrastructure development policies can enhance economic performance, particularly when combined with improvements in institutional quality and human capital development.